ANALYSIS OF IMPLEMENTATION OF LEARNING DEVICES DURING THE COVID-19 PANDEMIC ODD SEMESTER 20212022 at CINTA KASIH ELEMENTARY SCHOOL - Stefany Margareta Martono; Ester Caroline Wowor; Vina N Van Harling (SOSCIED, 2022)
Curriculum simplification is one of the ways in which the government supports education in Indonesia, so that learning can continue even during the COVID-19 pandemic. For this reason, the Cinta Kasih Elementary School simplifies learning tools in the odd semester of the 2021/2022 academic year so that competence can be achieved in each subject. Researchers carried out research with the aim of analyzing the simplification of learning tools during the COVID-19 pandemic in the 2021/2022 Odd Semester at Cinta Kasih Elementary School with a sample of learning tools for science and mathematics subjects in grade 4. This study used qualitative research, namely to see how effective the simplification of learning tools was. which was applied at the Cinta Kasih Elementary School by collecting data in the form of interview data, class visits and documentation during the learning process. The results of the study can be concluded that the simplification of learning tools can be carried out effectively in the odd semester, namely by looking at the condition of the school environment, the condition of the students, and most importantly, the creativity of the teacher in teaching and using time so that the competencies, indicators that have been designed can be achieved by students. The ability of students and teachers as well as the availability of infrastructure and facilities can be seen from the ability of students to capture in class, interaction in learning between teachers and students, use of learning media, and the availability of time used in learning. This is evidenced by taking interview data, scheduled class visits and supported by documentation taken in class, so it can be proven that the simplification of learning tools has been carried out during the covid-19 pandemic at Cinta Kasih Elementary School.